PENGARUH MOTIVASI KERJA, KOMUNIKASI KERJA DAN STRESS KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT. GRAMEDIA ASRI MEDIA MALL BALI GALERIA (MBG) BADUNG - Ni Ketut Rahayu; I Wayan Suarjana; Bagus Nyoman Kusuma Putra (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2023)
With good HR development or management, an employee can easily face and complete the demands of tasks both in the present and in the future. This study aims to determine the effect of work motivation, work communication, and work stress on employee job satisfaction. This research was conducted at PT. Gramedia Asri Media Mall Bali Galeria (MBG) Badung. The sample in this study were 55 employees at PT. Gramedia Asri Media Mall Bali Galeria (MBG) Badung. The method of determining the sample in this study is saturated sampling technique. Data collection was carried out through this study using linear regression analysis through the SPSS version 25 program. Based on the results of this research analysis shows that work motivation has a positive and significant effect on the performance of employees of PT. Gramedia Asri Media Mall Bali Galeria (MBG) Badung. The higher the level of work motivation of employees of PT. Gramedia Asri Media Mall Bali Galeria (MBG) Badung, the higher the employee job satisfaction. Work Communication has a positive and significant effect on the performance of employees of PT. Gramedia Asri Media Mall Bali Galeria (MBG) Badung. The better work communication that exists between employees and superiors of PT. Gramedia Asri Media Mall Bali Galeria (MBG) Badung, employee job satisfaction will increase. Work Stress has a negative and significant effect on the performance of employees of PT. Gramedia Asri Media Mall Bali Galeria (MBG) Badung. The higher the level of employee work stress, the higher the decline in employee work.